200 metre and 1000 metre sprint kayaking biomechanical analysis comparison using fixed and swivel seat: a pilot study - Lok, Y. L.; Smith, R.; Sinclair, P. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of the present study was to investigate the effects of using the standard fixed and swivel seat on the selected kinematic and kinetic parameters. It is conducted on a simulated 200 m and 1000 m race in the laboratory setting. One elite sprint kayaker participated in this study, performing both events and seat conditions on separate days. Paired sample t-tests and Pearson product-moment correlations were performed to compare seat conditions and relations between the parameters. High correlations were observed in paddle force with foot force, paddle power and paddle velocity. Significantly increased results were found in paddle force, paddle power and stroke rate using the swivel seat especially in the 1000 m test. Further research with more subjects is required for comparison to obtain important information of an efficient paddling execution.